Efficacy of lung surfactant combined with budesonide in improving bronchopulmonary dysplasia and growth of very low birth weight infants - Zhang, Yu; Liu, Ming; Li, Yue; Chi, Di; Zhang, Jinpu; Zhang, Yunfeng (Frontiers in Pediatrics, 2025)
BackgroundThere is few treatments for bronchopulmonary dysplasia (BPD), and systemic glucocorticoid therapy has serious side effects.MethodsLow birth weight infants were classified randomly into control group administered with pulmonary surfactant (200 mg/kg) and intervention group administered with pulmonary surfactant (200 mg/kg) and budesonide suspension (0.25 mg/kg) to explore the efficacy of combination of pulmonary surfactant and budesonide suspension is better than that of pulmonary surfactant alone.ResultsThe incidence of bronchopulmonary dysplasia was significantly lower in the intervention group (45%) compared to the control group (64%). Additionally, the duration of invasive ventilator use was significantly shorter in the intervention group (66.39 ± 37.09 h) than in the control group (82.05 ± 54.55 h); and the infants from the intervention group had a significantly shorter supplemental oxygen time, with the intervention group at 775.32 ± 396.06 h and the control group at 844.01 ± 414.18 h. Comparison of the basic conditions of the two groups of children showed no statistically significant differences in maternal medical history, gestational age, birth weight, sex, whether hormones were used prenatally, and delivery method (P > 0.05). There was no difference in the incidence of complications, such as neonatal infection, intracranial hemorrhage, necrotizing enterocolitis, and retinopathy between the two groups.ConclusionCombination of pulmonary surfactant with budesonide suspension can significantly decrease the incidence of bronchopulmonary dysplasia in very low birth weight infants, reduce the duration of invasive mechanical ventilation, and promote earlier weaning from oxygen supplement.Clinical Trial RegistrationEffect of budesonide combined with pulmonary surfactant on lung development in very low birth weight infants, ChiCTR2400086677, https://www.chictr.org.cn/showproj.html?proj=233373.